Sámi language teachers’ professional identities explained through narratives about language acquisition - Hammine, Madoka; Keskitalo, Pigga; Katjaana Sarivaara, Erika (The Australian Journal of Indigenous Education, 2019)
Abstract Conducted in northern Finland, this study examines Sámi language teachers’ professional identities through their narratives of language acquisition. We focus on how teachers’ professional identities are shaped by their language acquisition process. The results are based on the narratives of nine North, Inari and Skolt Sámi language teachers. Two aspects of teachers’ narratives were significantly linked to their identities as Sámi language teachers: (1) their backgrounds (indigenous/non-indigenous) and (2) their language acquisition experiences (acquired Sámi language in childhood/adulthood). Indigenous teachers appeared to express their professional identities strongly despite their challenging acquisition experiences and were inclined to work towards the future of Sámi languages. In addition, non-indigenous teachers were willing to further the development of Sámi languages although they are not indigenous, which perhaps contributes towards the future of Sámi languages. Teachers narrated complex thoughts about language acquisition and their professional identity and helped develop indigenous language education in their respective indigenous communities. We recommend that teachers’ in pre-service and service education should prepare and support indigenous language teachers by sharing knowledge about multilingual education practices and coping skills, particularly to help the latter manage varied tasks and heterogeneous contexts. Thus, this research study shows that both teachers’ language acquisition experiences and their current work situations shape their professional identity.